The Influence of Religiosity and Halal Labeling on Purchase Intention of Non-Food Halal Products - Susilawati, Cucu; Joharudin, Agus; Abduh, Muhamad; Sonjaya, Adang (Indonesian Journal of Halal Research, 2023)
The obligation to certify halal products in circulation is limited to food, beverages, goods, or services. This study determined the effect of halal labeling on the purchase intention of Indonesian Muslim communities in non-food halal products. Even though laws regulate halal products in circulation, not all people know about halal products, especially non-food products. This research method used a mixed method, which combined quantitative and qualitative methods. The design was a two-phase mixed method, with data collection techniques based on explanatory strategies. The results were analyzed with sequential data; quantitative was used as the basis for collecting qualitative data. The results of this study indicated there was a partially accepted influence of religiosity on Purchase Intention. Religiosity positively and significantly affected the Purchase Intention of non-food halal products. Furthermore, the hypothesis that said there was influence of the Perception of the Halal Label on Purchase Intention was partially accepted. Thus, the Perception of the Halal Label positively and significantly affected the Purchase Intention of non-food halal products. The significant level that produced 0.000, smaller than the specified significance level, was 0.05, so the significance level of Religiosity and Perception of Halal Labels was significant to Purchase Intention. It could also be seen that the f-count value was 118.210 with an f-table value of 3.1504, so the f-count > f-table or 118.210 > 3.1504, which means Religiosity and Perception of the Halal Label simultaneously affect Purchase Intention. In conclusion, Religiosity and Perception of the Halal Label simultaneously affect Purchase Intention on Non-Food Halal Products.